KARAKTERISTIK MALTODEKSTRIN PATI UMBI TALAS BENTUL (Colocasia esculenta L.) DAN KENTANG GRANULA KEMBANG (Solanum tuberosum L.) HASIL HIDROLISIS ENZIMATIS. - Rizki Tri Muhaimin; Warkoyo; Dahlia Elianarni (Universitas Muhammadiyah Malang, 2026)
Maltodextrin is a saccharide with a series of alpha-1,4 glycosidic bonds with a dextrose equivalent (DE) value of less than 20. Flower granule potato tubers and bentul taro have the potential to be used as raw materials in maltodextrin production because they have not been widely used. The purpose of this research was to produce maltodextrin from local tubers in Malang Raya, namely bentul taro and flower granule potato. This research was conducted at the Food Technology Laboratory of Muhammadiyah University of Malang with the help of α-amylase enzyme. The design used was factorial randomized group design (RAK) with factors of different starch masses (15 grams, 20 grams, 25 grams, and 30 grams) and starch sources (flower granule potato and bentul taro). The enzyme concentration used was 0.04% with a temperature of 60 oC for 90 minutes. The test results showed that the activity of commercial α-amylase enzyme was 67.22 U/mL, the starch content of flower granule potato raw material was 26.17% total starch, amylose content was 4.05%, and amylopectin content was 22.12%. Meanwhile, the bentul taro raw material obtained a total starch content of 24.23%, amylose content of 1.75%, and amylopectin content of 22.48%. The best results of the research obtained from the values that often appear are flower granule potato maltodextrin with a starch weight of 20 grams with a yield of 47.74%, DE value of 11.47, pH 6, 05, and swelling power of 6.22%, solubility of 81.02%, color parameter L 82.67, parameter a 2.2, and parameter b 2.3.